Deep obstructive nabothian cyst in pregnancy mimicking adenocarcinoma on magnetic resonance imaging: an obstetricians dilemma - Naik, Parvathi T.; Maurya, Dilip K.; Jinkala, Sreerekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Nabothian cysts are benign mucous retention cysts of the cervix, most commonly seen in women of reproductive age. However, large Nabothian cysts may have a variable presentation and can even mimic malignancy, causing diagnostic dilemmas, especially during pregnancy. The case highlights the deep obstructive nature of the Nabothian cyst, which can mimic malignancy and must be differentiated from the invasive cervical lesion.